Improvement of anxiety in ADHD following goal-focused cognitive remediation: a randomized controlled trial - Hanssen, Kjersti T.; Brevik, Erlend J.; Småstuen, Milada C.; Stubberud, Jan (Frontiers in Psychology, 2023)
Despite the high prevalence and detrimental consequences of cognitive and executive dysfunction in ADHD, the evidence base of cognitive remediation in the adult ADHD population is sparse. Executive problems can increase both anxiety and depression in ADHD. Thus, it is important to develop treatment options for adults with ADHD, aiming to improve goal-directed behavior and mood. Goal Management Training (GMT) is an intervention that has received empirical support in improving executive functions and mood in normal aging and for various neurological and psychiatric conditions. The present randomized controlled trial investigated the effects of a goalfocused intervention combining 1) group-based GMT incorporating psychoeducation about ADHD and 2) guidance in implementing individual goals for coping with executive problems in everyday life, compared to treatment as usual (TAU). The primary outcome was perceived executive functioning in everyday life. Secondary outcomes included psychological well-being (anxiety, depression, and coping with ADHD symptoms). We recruited 81 adult participants with a verified ADHD diagnosis (Mage= 31 years). Inclusion was based upon the presence of executive functioning complaints. The participants were randomly assigned to either the intervention or TAU. The intervention group (n=41) received 16 hours of GMT and psychoeducation, in addition to 4 individual sessions focusing on formulating goals. The goals were assessed in 6 bi-weekly phone calls in the first three months following the group sessions. Participants in the TAU group (n=40) received standard, individually-adapted follow-up in an outpatient psychiatric health care setting. All participants were assessed at baseline, post-intervention, and at 8-month follow-up (main measurement time point). Significant improvements in everyday executive functioning, psychological well-being, and symptoms of ADHD from baseline to 8-month follow-up were reported in both groups. The intervention group reported a significantly higher reduction in symptoms of anxiety compared to TAU. Our findings provide support for considering cognitive remediation as a treatment option for patients with ADHD.